11C-PET imaging reveals transport dynamics and sectorial plasticity of oak phloem after girdling - De Schepper, Veerle; Bühler, Jonas; Thorpe, Michael; Roeb, Gerhard; Huber, Gregor; van Dusschoten, Dagmar; Jahnke, Siegfried; Steppe, Kathy (Frontiers in Plant Science, 2013)
Carbon transport processes in plants can be followed non-invasively by repeated application of the short-lived positron-emitting radioisotope 11C, a technique which has rarely been used with trees. Recently, positron emission tomography (PET) allowing 3D visualisation has been adapted for use with plants. To investigate the effects of stem girdling on the flow of assimilates, leaves on first order branches of two-year-old oak (Quercus robur L.) trees were labelled with 11C by supplying 11CO2-gas to a leaf cuvette. Magnetic resonance imaging gave an indication of the plant structure, while PET registered the tracer flow in a stem region downstream from the labelled branches. After repeated pulse labelling, phloem translocation was shown to be sectorial in the stem: leaf orthostichy determined the position of the phloem sieve tubes containing labelled 11C. The observed pathway remained unchanged for days. Tracer time-series derived from each pulse and analysed with a mechanistic model showed for two adjacent heights in the stem a similar velocity but different loss of recent assimilates. With either complete or partial girdling of bark within the monitored region, transport immediately stopped and then resumed in a new location in the stem cross-section, demonstrating the plasticity of sectoriality. One day after partial girdling, the loss of tracer along the interrupted transport pathway increased, while the velocity was enhanced in a non-girdled sector for several days. These findings suggest that lateral sugar transport was enhanced after wounding by a change in the lateral sugar transport path and the axial transport resumed with the development of new conductive tissue